2020
DOI: 10.5114/pjr.2020.93364
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of intraocular optic nerve disorders: review article

Abstract: The optic nerve is morphologically classified as a peripheral nerve, but histologically it shares characteristics with the central nerves. Diseases that affect vision and the optic nerve are many and varied: optic neuritis, demyelination (multiple sclerosis, acute disseminated encephalomyelitis, neuromyelitis optica spectrum disorder, and myelin oligodendrocyte glycoprotein antibody-related disorders), drugs, collagen disease, vasculitis, infection, trauma, vascular abnormalities, tumours, and non-tumoural mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It has been suggested that both water and fat signals should be suppressed. 5 , 64 For MRI magnetic field strength, 1.5T or 3T is recommended. 5 In the acute phase, the optic nerve is enlarged with a high-intensity signal on T2-weighted imaging and has a contrast effect on post-contrast-enhanced T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that both water and fat signals should be suppressed. 5 , 64 For MRI magnetic field strength, 1.5T or 3T is recommended. 5 In the acute phase, the optic nerve is enlarged with a high-intensity signal on T2-weighted imaging and has a contrast effect on post-contrast-enhanced T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 64 For MRI magnetic field strength, 1.5T or 3T is recommended. 5 In the acute phase, the optic nerve is enlarged with a high-intensity signal on T2-weighted imaging and has a contrast effect on post-contrast-enhanced T1-weighted imaging. 5 This study is the first systematic review and meta-analysis on the differences in lesion sites among different DON subtypes during a conventional MRI scan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O ptic neuritis (ON) is characterized by inflammation of the optic nerve which is mainly idiopathic demyelination. Also, many causes including ischemic, metabolic, nutritional, hereditary, toxic, traumatic, paraneoplastic and radiation induced events [1]. Clin-ical presentation of the optic neuritis is mostly visual loss, periocular pain and dyschromatopsia of triple semptoms, and some patients may suffer from visual field defects and swelling or atrophy of the optic nerve [2,3].…”
mentioning
confidence: 99%